2018
DOI: 10.1038/s41598-018-33982-y
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Mcl-1 expression by the CDC7/CDK9 inhibitor PHA-767491 overcomes bone marrow stroma-mediated drug resistance in AML

Abstract: Acute myeloid leukaemia (AML) is an aggressive cancer with 50–75% of patients relapsing even after successful chemotherapy. The role of the bone marrow microenvironment (BMM) in protecting AML cells from chemotherapeutics and causing consequent relapse is increasingly recognised. However the role that the anti-apoptotic Bcl-2 proteins play as effectors of BMM-mediated drug resistance are less understood. Here we show that bone marrow mesenchymal stromal cells (BMSC) provide resistance to AML cells against BH3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…There are various studies that have successfully associated CDK9 inhibition with MCL-1 depletion and subsequent induction of tumor cell death (41). However, many come with study design caveats such as prolonged CDK9 inhibition (15,42), a narrow focus on one indication and/or a limited number of preclinical models (8,43), and use of nonselective compounds (14,44) that make it difficult to draw firm conclusions. This study overcame those limitations by utilizing the selective CDK9 inhibitor, AZD4573, and applying multiple approaches to interrogate the mechanism of action of CDK9 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…There are various studies that have successfully associated CDK9 inhibition with MCL-1 depletion and subsequent induction of tumor cell death (41). However, many come with study design caveats such as prolonged CDK9 inhibition (15,42), a narrow focus on one indication and/or a limited number of preclinical models (8,43), and use of nonselective compounds (14,44) that make it difficult to draw firm conclusions. This study overcame those limitations by utilizing the selective CDK9 inhibitor, AZD4573, and applying multiple approaches to interrogate the mechanism of action of CDK9 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…With the ability to resist apoptosis, Mcl-1 exerts its impact either by isolating Bak on the outer mitochondrial membrane or by heterodimerizing with stimulated Bcl-2 homology domain 3-only proteins, such as p53-upregulated modulator of apoptosis, Bim and tBid (39). Mcl-1 expression is found in various types of OC cells (40,41), and multiple triggers outside of the cells, such as interleukins, 12-o-tetradecanoyl-phorbol-13-acetate, growth factors and interferons, are able to upregulate Mcl-1 expression by stimulating several pathways (42). It has been previously reported that Mcl-1 downregulation by antisense oligonucleotides is sufficient to trigger apoptosis of OC cells and enhance sensitivity to tumor necrosis factor-related apoptosis-inducing ligand, thus indicating that Mcl-1 is a promising target to treat malignancies such as OC (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Selective inhibition of CDC7 suppresses proliferation of transformed cells through induction of S-phase delay and replication stress ( Cheng et al., 2018 , Im and Lee, 2008 , Ito et al., 2012 , Iwai et al., 2019 , Montagnoli et al., 2004 ). Furthermore, CDC7 antagonists showed promise in combination with other cell-cycle inhibitors and anti-cancer therapeutics ( Cao and Lu, 2019 , Gad et al., 2019 , O' Reilly et al., 2018 ). Selective inhibitors of CDC7 are being developed and trialed as anti-cancer therapeutics, with a number of candidate drugs undergoing clinical trials ( Cheng et al., 2018 , Gallagher et al., 2019 , Huggett et al., 2016 , Iwai et al., 2019 , Koltun et al., 2012 , Kurasawa et al., 2020 , Sawa and Masai, 2009 , Swords et al., 2010 , Vanotti et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%